Development and characterisation of packing, microstructural, physico‐ and phytochemical attributes of potential functional jamun (Syzygium cumini L.)pomace powder for direct compression: high antioxidant nutraceutical tablets. (4th July 2022) - Kaur, Navjot; Aggarwal, Poonam
Summary: This study aimed at drying jamun pomace; a rich source of bioactive compounds and utilising it for development of phytonutrient and antioxidant‐rich nutraceutical tablets by mixing with ultrasonically extracted pomace extract. Packing, microstructural, physico‐ and phytochemical properties of the powders produced by freeze drying, hot air drying were evaluated. Freeze‐dried powder showed better flowability, lower Hausner ratio and less hygroscopicity. Phytochemicals of freeze‐dried powder were approximately 15% higher than cabinet dried powder, further confirmed using Fourier transform infrared (FTIR) analysis, while producing more uniform particles as confirmed using SEM and particle size distribution. The freeze‐dried powder was further mixed with ultrasonically extracted pomace extract (using distilled water acidified with citric acid as solvent) in the ratio 1:1 (w/v) to increase phytonutritional profile and compressed to form tablets, which showed rapid disintegration and in vitro release of anthocyanins. Storage studies (at 25 ± 2 °C/50%–88% RH) revealed that the moisture and water activity significantly ( P  < 0.05) increased while approximately 76% phytochemicals and 81.20% antioxidant activities were retained at the end of four months. In the nutshell, the formulation of nutraceutical tablets with good bioavailability cannot only help in the effective utilisation of jamun waste but also provide nutraceutical product. High antioxidant jamun pomace nutraceutical tablets: